DOI: 10.18174/503185
|View full text |Cite
|
Sign up to set email alerts
|

Feed the crop, not the soil! : Explaining variability in maize yield responses to nutrient applications in smallholder farms of western Kenya

Abstract: With references, with summaries in English and Dutch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 131 publications
(316 reference statements)
1
3
0
Order By: Relevance
“…Farm-level yields obtained during the programme (measured) aligned with yields from earlier field-level experimental work in western Kenya by Njoroge et al [ 17 ] and Vanlauwe et al [ 20 ] and were larger than the relatively poor yields described by Roobroeck et al [ 67 ], in particular during the long rains cropping seasons. The immediate response to increased input use as found in our study was similar to the response found by Njoroge [ 68 ] in western Kenya, when they applied full fertilisation after eight seasons of no or unbalanced fertilisation. During monitoring of input use we did not observe any new subsidy schemes or other changes in input availability in our research locations.…”
Section: Discussionsupporting
confidence: 89%
“…Farm-level yields obtained during the programme (measured) aligned with yields from earlier field-level experimental work in western Kenya by Njoroge et al [ 17 ] and Vanlauwe et al [ 20 ] and were larger than the relatively poor yields described by Roobroeck et al [ 67 ], in particular during the long rains cropping seasons. The immediate response to increased input use as found in our study was similar to the response found by Njoroge [ 68 ] in western Kenya, when they applied full fertilisation after eight seasons of no or unbalanced fertilisation. During monitoring of input use we did not observe any new subsidy schemes or other changes in input availability in our research locations.…”
Section: Discussionsupporting
confidence: 89%
“…It is grown by over 3 million smallholder farmers, accounting for 70% of the nation's output (D'Alessandro et al., 2015). In recent years, maize production has encountered many challenges, including the high cost of inputs, declining soil fertility, pest and disease invasions, and poor coordination of extension service delivery (Kinyanjui, 2019; Tittonell et al., 2008). The challenges faced by rainfed maize production are further exacerbated by climate change (Salami et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen use efficiency and N surplus Nitrogen (N) use efficiency of maize was calculated at farm level per season: the total N outputs in maize grain (kg N ha -1 ) divided by the N inputs on all fields with maize (kg N ha -1 ). N output was calculated using the weighted average maize grain yield per farm and a fixed N content in maize grain of 1.54% (Njoroge, 2019). A farm level weighted average for N inputs was calculated based on the mineral fertiliser used per field, as reported in the monitoring survey.…”
Section: Environmentmentioning
confidence: 99%
“…However, when good yields and thereby soil N mining are continued, N and other nutrients (e.g. K) may become limiting (Njoroge, 2019) and fertilizer rates needs to be adjusted.…”
Section: Efference Of Concurrent Pathways Of Intensification and Extensificationmentioning
confidence: 99%